2022
DOI: 10.1002/adma.202109091
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Changing DNA‐Linked Nanoparticle Films Dictated by Lateral and Vertical Patterns

Abstract: The self‐assembly of nanoscale building blocks into complex nanostructures with controlled structural anisotropy can open up new opportunities for realizing active nanomaterials exhibiting spatiotemporal structural transformations. Here, a combination of bottom‐up DNA‐directed self‐assembly and top‐down photothermal patterning is adopted to fabricate free‐standing nanoparticle films with vertical and lateral heterogeneity. This approach involves the construction of multicomponent plasmonic nanoparticle films b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The NP film was made up of stacks of domains, each composed of particles with different plasmonic properties and grafted with a different combination of DNA sequences. Compared with the traditional lithography technique of sequential etching, this strategy can control the laser to change the selective removal of target regions in the film, so that the selected DNA sequence carrying information can shrink and expand in a programmable way, resulting in highly oriented structural deformation [ 64 ]. In another case, Mitta et al prepared AuNPs by drop-casting and embedded them into DNA films to obtain composite films with high stability and enhanced response to UV light, indicating that 2D DNA films can be used as carriers for the modification and functionalization of biomimetic nanomaterials [ 65 ].…”
Section: Biomolecular Functional Nanomaterialsmentioning
confidence: 99%
“…The NP film was made up of stacks of domains, each composed of particles with different plasmonic properties and grafted with a different combination of DNA sequences. Compared with the traditional lithography technique of sequential etching, this strategy can control the laser to change the selective removal of target regions in the film, so that the selected DNA sequence carrying information can shrink and expand in a programmable way, resulting in highly oriented structural deformation [ 64 ]. In another case, Mitta et al prepared AuNPs by drop-casting and embedded them into DNA films to obtain composite films with high stability and enhanced response to UV light, indicating that 2D DNA films can be used as carriers for the modification and functionalization of biomimetic nanomaterials [ 65 ].…”
Section: Biomolecular Functional Nanomaterialsmentioning
confidence: 99%
“…Shape change of ultrathin films can be directed using DNA signals (25)(26)(27). DNA sequences can also swell or shrink hydrogels (17,18,(28)(29)(30)(31), but afterward, these hydrogels are no longer responsive to DNA instructions.…”
Section: Main Textmentioning
confidence: 99%
“…[52] The planetary nano-gearsets are formed by connecting two DNA origami rings and cross-linking two Au nanoparticles in between. Kim et al demonstrated that photopatterning of DNAdirected Au nanorod self-assembled films is possible by the photothermal effect when illuminated by a laser [53] . As the illuminated spots heat up due to the photothermal effect, the disentanglement of the nanoparticles from the DNA linkage is possible by the application of a laser of sufficient intensity and suitable wavelength, Figure 4 (c).…”
Section: 13mentioning
confidence: 99%
“…Photothermal heating of the illuminated spots facilitates unlinking of the nanoparticles. Reprinted with permission [53] © 2022 John Wiley & Sons.…”
Section: 13mentioning
confidence: 99%